Impact of Social Audit on the Performance of MGNREGS: A Study in Tamilnadu and Karnataka - R.Chinnadurai and .R.Arunajayamani (KILA Journal of Local Governance, 2015)
Governments are facing an ever growing demand for more accountable and socially responsible. The people are becoming more assertive about their rights to be informed and to influence Governments1 decision making processes. After few years of effective implementation of the National Rural Employment Guarantee Act, 2005, the Government insists every State to conduct social audit to understand the financial and physical performance. Social audit has been carried out in various States on MGNREGS. In addition to the fact finding results, the social audit made tremendous impact on the creation of awareness to the beneficiaries on the provisions and entitlements of the schemes. This research was aimed to validate the process of social audit conducted, its usefulness in terms of physical and financial achievements and ultimately impact on programme implementation.